Jihadi Audiovisuality and Its Entanglements : Meanings, Aesthetics, Appropriations - Günther, Christoph (Middle East specialist); Pfeifer, Simone (Edinburgh University Press, 2020)
Explores the use of images, sounds and videos in Jihadi media and how people engage with them.